EFL teachers - Putu Wiraningsih; Made Hery Santosa (Journal on English as a Foreign Language, 2020)
Teachers have a responsibility to help students become autonomous learners. However, in promoting learner autonomy, the teachers were faced with the challenges. This descriptive qualitative study aimed to describe the challenges in promoting learner autonomy in 21st-century learning faced by EFL teachers and their strategies. The data were collected through a semi-structured interview technique. Four qualified EFL junior high school teachers with at least five years of teaching experience in Singaraja Bali Indonesia were involved. The interview guideline was constructed based on the dimensions of policy constraints, institutional constraints, language teaching methodology, and learner's background. The interviews were transcribed and categorized into the table of identification based on the four dimensions. Finally, the data regarding the challenges and the strategies were interpreted, and the excerpts of the interview were provided.